PROBLEM PATOLOGI SOSIAL PENGEMIS SEBAGAI KELOMPOK MARGINAL PENGUMPUL KEUNTUNGAN - Mahatva Yoga Adi Pradana; Muhammad Fiqri Fadilah (Kopertais Wilayah III Yogyakarta, 2022)
Abstract Humans are born into the world in a state of nature, which means that not a single human being from birth can be called a pathology or a disease of society. Phenomena that occur in the existing environment cause humans to be able to influence and shape human character and personality. For example, with the increasingly rapid development of the times and humans who have not been able to adapt, they can take practical actions to adapt to their environment. So that from there some social problems emerge which, if the problem is allowed to continue, can form pathological problems that exist in society. This problem is related to the increasing number of people who beg with the stigma of being beggars. Moreover, this phenomenon is used as a profit commodity. The author uses a qualitative study with a social approach in it. Finally, the authors get a new understanding of how beggars become a marginalized group which is considered a pathological problem. Until finally this phenomenon can be resolved with the empowerment of marginalized communities. Keywords: Marginal, Social Pathology, Beggars